2016
DOI: 10.1093/molbev/msw068
|View full text |Cite
|
Sign up to set email alerts
|

TriLoNet: Piecing Together Small Networks to Reconstruct Reticulate Evolutionary Histories

Abstract: Phylogenetic networks are a generalization of evolutionary trees that can be used to represent reticulate processes such as hybridization and recombination. Here, we introduce a new approach called TriLoNet (Trinet Level- one Network algorithm) to construct such networks directly from sequence alignments which works by piecing together smaller phylogenetic networks. More specifically, using a bottom up approach similar to Neighbor-Joining, TriLoNet constructs level-1 networks (networks that are somewhat more g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…These clusters are congruent with the lineages detected by the Bayesian phylogeny (Figure a). The level‐1 network further unraveled the following three reticulation events (Figure b) (a) the entire clade F resulted from reticulation between a parent belonging to a subtype of the viviparous clade D and a parent belonging to a subtype of the oviparous clade A; reticulation existed; (b) within clade A (green cluster); and (c) within the Ibero‐Pyrenean clades (note: excluding the reticulated species B1_09_503; Oldman et al, led to two clades within the violet Iberio‐Pyreanean clade, consisting of a cluster containing B2 and a cluster containing B3 and B1; which is congruent with the Bayesian phylogeny; see also Text S1). The network thus suggests that viviparity evolved once and that clade B might be a reversal.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…These clusters are congruent with the lineages detected by the Bayesian phylogeny (Figure a). The level‐1 network further unraveled the following three reticulation events (Figure b) (a) the entire clade F resulted from reticulation between a parent belonging to a subtype of the viviparous clade D and a parent belonging to a subtype of the oviparous clade A; reticulation existed; (b) within clade A (green cluster); and (c) within the Ibero‐Pyrenean clades (note: excluding the reticulated species B1_09_503; Oldman et al, led to two clades within the violet Iberio‐Pyreanean clade, consisting of a cluster containing B2 and a cluster containing B3 and B1; which is congruent with the Bayesian phylogeny; see also Text S1). The network thus suggests that viviparity evolved once and that clade B might be a reversal.…”
Section: Resultsmentioning
confidence: 95%
“…Consequently, two possible scenarios of parity mode evolution exist: (a) a single evolution of viviparity (in the ancestor of Anableps and the violet cluster in Figure a) and two potential reversals from viviparity to oviparity, in the ancestor of Tomeurus gracilis and in the ancestor of Oxyzygonectes dovii , or (b) multiple evolution of viviparity (i.e., at least three times, in the ancestor of Jenynsia and Anableps, in the ancestor of Xenodexia, and in the ancestor of the other viviparous species—the ancestor of the violet cluster in Figure a). Testing for reticulation using TriLoNet (Oldman et al, : see Text S1 for detailed methodological details) revealed three clusters in the level‐1 network (Figure b), the gray cluster including Cyprinodon and Jordanella, the green cluster including Fluviphylax, Aplocheilichthys, Oxyzyogonectes, Jenynsia, Anableps, and Xenodexia; and the violet cluster including the remaining species (Figure b). These clusters coincided with the clusters of the Bayesian phylogeny (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2016). In particular, for a set X of species, a network is constructed for every subset of X size 3 (called a trinet ), and then the trinets are puzzled together to build a network (see Fig.…”
Section: Introductionmentioning
confidence: 99%